Analisis Pengaruh Experiential Marketing terhadap Kepuasan Pelanggan Pada E- Resto Semarang - Noviarini, Amanda Pramesty; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2014)
This research is motivated by the increasing level of customer complaints and followed by a declining number of subscriber in a row at E - Resto Semarang . This research effort undertaken to review the E - Resto to improve overall customer satisfaction using experiential marketing elements and become flagship restaurant in Semarang . The effort by E-Resto so far to improve customer satisfaction are unconditional guarantee for its food and drink and efficient complain handling by taking their guest comment positively. This study examines the elements of experiential marketing which consists of sense , feel , think, act and relate that affect customer satisfactionThrough the questionnaire method using techniques purposive sampling to 100 respondents who ever came and mergkonsumsi E - Resto Semarang products showed the regression equation as follows :Y = 0.202 X1 + 0.187 X2 + 0.199 X3 + 0.203 X4 + 0.188 X5Where all the independent variables have a positive and significant impact on customer satisfaction. Figures Adjusted R Square of 0.594 indicates that 59.4 percent of the variation can be explained by the Customer Satisfaction to - five independent variables in the regression equation . While the remaining 40.6 percent is explained by other variables outside the five variables used in this study.